2022
DOI: 10.3390/ma15196524
|View full text |Cite
|
Sign up to set email alerts
|

Compressive Mechanical Properties and Shock-Induced Reaction Behavior of Zr/PTFE and Ti/PTFE Reactive Materials

Abstract: Existing research on PTFE-based reactive materials (RMs) mostly focuses on Al/PTFE RMs. To explore further possibilities of formulation, the reactive metal components in the RMs can be replaced. In this paper, Zr/PTFE and Ti/PTFE RMs were prepared by cold isostatic pressing and vacuum sintering. The static and dynamic compressive mechanical properties of Zr/PTFE and Ti/PTFE RMs were investigated at different strain rates. The results show that the introduction of zirconium powder and titanium powder can increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The modified Hall–Petch model was obtained, with the obtained value of K twin serving as an effective metric for this relationship. Zhang et al [ 2 ] prepared Zr/PTFE and Ti/PTFE composites via cold isostatic pressing and vacuum sintering. They investigated the static and dynamic compressive mechanical properties of these composites at various strain rates.…”
Section: Dynamic Mechanical Properties and Constitutive Model Of Mate...mentioning
confidence: 99%
See 1 more Smart Citation
“…The modified Hall–Petch model was obtained, with the obtained value of K twin serving as an effective metric for this relationship. Zhang et al [ 2 ] prepared Zr/PTFE and Ti/PTFE composites via cold isostatic pressing and vacuum sintering. They investigated the static and dynamic compressive mechanical properties of these composites at various strain rates.…”
Section: Dynamic Mechanical Properties and Constitutive Model Of Mate...mentioning
confidence: 99%
“…This controlling mechanism indicated that oxides enhanced the reaction after shock wave unloading, and the chemical and physical properties of the corresponding thermites also affected the energy release characteristics. These conclusions can guide the design of metal/fluoropolymer-based RMs [ 2 , 9 , 10 ].…”
Section: Shock-induced Chemical Reactionmentioning
confidence: 99%
“…Huang et al [ 10 ] established the Johnson–Cook constitutive model of PTFE/Al/MoO 3 , and the model results agreed well with the experimental data. Zhang et al [ 11 ] proposed a modified Johnson–Cook model considering strain and strain-rate coupling, and the parameters of the modified Johnson–Cook model of Zr/PTFE and Ti/PTFE reactive materials were determined, which can describe and predict plastic flow stress. Zhang et al [ 12 ] determined the Johnson–Cook constitutive constants of PTFE/Al/W, and the predicted stress–strain response at elevated strain rates and temperatures agreed well with the tested results.…”
Section: Introductionmentioning
confidence: 99%